2018
DOI: 10.3390/su10041271
|View full text |Cite
|
Sign up to set email alerts
|

Member Heterogeneity in Agricultural Cooperatives: A Systems-Theoretic Perspective

Abstract: All over the globe, cooperatives are plagued by pervasive member heterogeneity problems that are induced by the radical and dynamic changes in the business environment. Most current solutions to these problems emphasize strengthening member loyalty and commitment. Yet, many of these solutions are symptomatic rather than fundamental. Searching for fundamental solutions, this paper draws on the Luhmannian system-environment paradigm. Bringing this paradigm to bear on the cooperative scholarship, the paper views … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 51 publications
(80 reference statements)
1
19
0
2
Order By: Relevance
“…In the case of supply cooperatives, farmers' relationship with their AC fits more that of a consumer or buyer in a purchasing group. These findings are in line with those of from economic studies of ACs, which have found these cooperative organisations are developing similar managerial hierarchies to that of private companies (Iliopoulos and Valentinov, 2018), and losing social capital as a result (Nilsson et al, 2012).…”
Section: The Importance Of Language: How "Cooperative" Is Still a Polsupporting
confidence: 91%
“…In the case of supply cooperatives, farmers' relationship with their AC fits more that of a consumer or buyer in a purchasing group. These findings are in line with those of from economic studies of ACs, which have found these cooperative organisations are developing similar managerial hierarchies to that of private companies (Iliopoulos and Valentinov, 2018), and losing social capital as a result (Nilsson et al, 2012).…”
Section: The Importance Of Language: How "Cooperative" Is Still a Polsupporting
confidence: 91%
“…When researchers write about membership heterogeneity, there are different interpretations. On the one hand, such heterogeneity may imply problems such as costs of decision-making, postponement of urgent decisions, or favourable treatment of a specific group of members [40]. On the other hand, membership heterogeneity may be positive, if two or more member categories have supplementary attributes and if the member categories have sufficiently strong social relations to acknowledge that they are interdependent [41].…”
Section: Chinese Agricultural Cooperativesmentioning
confidence: 99%
“…In particular, agricultural cooperatives represent an answer to the global challenges that have seen farmers as victims of the market in agreements [48]. Indeed, cooperative theory advocates the preeminence of specific stakeholders, such as members and an organizational board, and thus the investigation of the dynamics of conflicts [49]. Therefore, cooperatives in agricultural areas have increasingly involved stakeholders as key actors.…”
Section: Investigating the Agricultural Cooperatives And Replying To mentioning
confidence: 99%